2017
DOI: 10.1002/mus.25680
|View full text |Cite
|
Sign up to set email alerts
|

The conventional tuning fork as a quantitative tool for vibration threshold

Abstract: Introduction: This study was undertaken to describe a method for quantifying vibration when using a conventional tuning fork (CTF) in comparison to a Rydel-Seiffer tuning fork (RSTF) and to provide reference values. Methods: Vibration thresholds at index finger and big toe were obtained in 281 participants. Spearman's correlations were performed. Age, weight, and height were analyzed for their covariate effects on vibration threshold. Reference values at the fifth percentile were obtained by quantile regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As seen in other sensory and neuropsychological assessments [11][12][13][14], performance declined with older age and with less education. Only the oldest age group demonstrated a decline in performance, it is possible that decline in the number of nerve fascicles or functional receptors and reductions in central processing speed may be responsible [11][12][13][14]. Similarly, lower education level was associated with lower performance, as is demonstrated in most neuropsychological assessments [14].…”
Section: Discussionmentioning
confidence: 95%
“…As seen in other sensory and neuropsychological assessments [11][12][13][14], performance declined with older age and with less education. Only the oldest age group demonstrated a decline in performance, it is possible that decline in the number of nerve fascicles or functional receptors and reductions in central processing speed may be responsible [11][12][13][14]. Similarly, lower education level was associated with lower performance, as is demonstrated in most neuropsychological assessments [14].…”
Section: Discussionmentioning
confidence: 95%
“…Cutaneous vibration sensation was evaluated by using a 128 Hz tuning fork (Rydel-Seiffer graduated tuning fork, Martin Tuttlingen, Germany) at the first metatarsal head and medial malleolus bilaterally (McLaughlin et al, 2005;Citaker et al, 2011). This is a reliable and valid clinical tool that is used to evaluate vibration perception impairments (Alanazy et al, 2018;Marcuzzi et al, 2019). The duration of the perceived vibration stimulus (average of three trials) for each site was recorded.…”
Section: Somatosensory Functionmentioning
confidence: 99%
“…It is possible that the clinical measurements lack the resolution to demonstrate continuous relationships. For example, it has been shown that the relationship between the tuning fork vibration time and age only degrades about 5 s from the age of 20–60 on average (Alanazy, Alfurayh, Almweisheer, Aljafen, & Muayqil, ). It is therefore unreasonable to expect to see this relationship in a small cohort with a limited age range, and when tuning fork time is summarized into 5‐s blocks.…”
Section: Discussionmentioning
confidence: 99%